Implementation of Compliance Testing Program on a Direct Digital Radiography (DDR) X-Ray System at the Radiography and Imaging Laboratory of the Health Polytechnic Ministry of Health Semarang - Gatot Murti Wibowo; Rasyid Rasyid; Ahkmad Haris Sulistiyadi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
Technological evolution from conventional to digital in diagnostic imaging bring a change in the implementation of Quality Control (QC) of radiology. As a part of the Quality Assurance (QA), QC Radiology is implemented to determine the eligibility condition of the radiography equipment used for the radiological examinations. A Direct Digital Radiography (DDR) unit has been installed in Radiography Laboratory (Lab 3), School of Radiodiagnostic and Radiotherapy, the Health Polytechnic of Semarang since February 2013. However, routine performance tests of the equipment have never been performed. This study aimed to obtain baseline data by assessing the equipment parameters of the X-ray and the digital-DDR systems (illumination collimator; collimator accuracy; beam alignment; tube leakage; kVp accuracy; timer accuracy; mA linearity; reproducibility; HVL, and dark image; nonuniformity; noise; bad pixels; lag respectively). Accuracy and reproducibility of the DDR unit were measured following the procedure of Perka Bapeten No. 9-2011 (for X-ray System) and IEC 62220-1: 2003 (for digital system. Data were analyzed descriptively by QC-DR software. Results showed that X-rays system and digital system had overall good performance. Signal non-uniformity was found in the value of Local Signal to Noise Ratio (LSNRNU) and Global Signal to Noise Ratio (GSNRNU. Non-uniformity caused by the characteristics of the detector and the lack of correction in system performance. Signal correction software needed to be developed to reach signal uniformities. Spatial resolution and low contrast detectability testing also needed to be performed to ensure the ability of the DDR unit to produce image resolution and contrast picture of the object.